The Impact of Information Sharing on Supply Chain Performance under Asymmetric Information - Inderfurth, Karl; Sadrieh, Abdolkarim; Voigt, Guido (Production and Operations Management, 2013)
The use of screening contracts is a common approach to solve supply chain coordination problems under asymmetric information. One main assumption in this context is that managers without specific incentives would rather use their private information strategically than reveal it truthfully. This harms supply chain performance. This study investigates the impact of information sharing in a principal‐agent setting that is typical for many supply chain transactions. We conduct a laboratory experiment to test whether information sharing has an influence on supply chain coordination. We find that information sharing within the supply chain has two positive effects. First, information sharing reduces the inefficiencies resulting from information deficits if there is a certain amount of trust in the supply chain. Second, communication can limit out‐of‐equilibrium behavior with a small impact on the firm's own payoff, but a large impact on the supply chain partner. Furthermore, we find that both effects are amplified when communication takes place in an environment that allows the less informed supply chain party to punish or to reward the better informed party. Although our extended mechanisms substantially enhance the poor performance of the theoretically optimal coordination contract menu, we find no mechanism that implements supply chain performance superior to the theoretically predicted second‐best level.